C-band ultra-low loss self-biased hexagonal spin-magnetic ferrite material and preparation method thereof

By growing LaScBiCu-BaM hexagonal rotary magnetite material on the surface of BiCaZrVIn-YIG rotary magnetite particles, combined with multiple regulatory mechanisms, the problem that existing materials are difficult to have multiple high-performance characteristics is solved, and the low loss bandwidth expansion requirement of C-band micro-integrated devices is achieved.

CN119176714BActive Publication Date: 2025-04-18UNIV OF ELECTRONICS SCI & TECH OF CHINA
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202411368264.2
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-09-29
Publication Date
2025-04-18
Estimated Expiration
2044-09-29

Smart Images

  • Figure CN119176714B_ABST
    Figure CN119176714B_ABST
Patent Text Reader

Abstract

A C-band ultra-low loss self-biased hexagonal gyromagnetic ferrite material belongs to the technical field of ferrite material preparation. The ferrite material includes BiCaZrVIn‑YIG gyromagnetic ferrite material and LaScBiCu‑BaM hexagonal gyromagnetic ferrite material in a weight ratio of 0.1 to 10; the weight percentage of the dopant in the ferrite material, calculated as oxide: 0.3 to 0.7wt% La2O3, 0.4 to 0.8wt% SiO2 and 0.5 to 0.9wt% SrTiO3. The present invention grows a high M hexagonal ferrite on the surface of low-loss BiCaZrVIn‑YIG gyromagnetic ferrite particles. r / M s and H c The LaScBiCu‑BaM hexagonal ferrite with high and adjustable anisotropy field H a , high coercivity H c and remanence ratio M r / M s , ultra-low ferromagnetic resonance linewidth △H and dielectric loss tanδ ε The characteristic hexagonal spin magnetic ferrite material meets the engineering requirements of low loss and wide bandwidth for C-band micro-integrated devices.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of ferrite material preparation, and particularly relates to a C-band ultra-low loss self-biased hexagonal spin-magnetic ferrite material and a preparation method thereof. Background Art

[0002] Promoting the sustainable development of the mobile communications industry is the key to supporting the country's digital transformation. The C-band (4-8GHz) can take into account the coverage advantages of low frequencies and the capacity advantages of high frequencies, and achieve continuous allocation of large-bandwidth spectrum of hundreds of megahertz at a lower cost per bit, meet the future demand for greater data traffic, and accelerate the process of social digital transformation. The use of the C-band has greatly increased the number of MIMO channels, but the expansion of the number of channels will also significantly increase the number of circulators, the core components in the base station transceiver components. Traditional circulators are based on spinel or garnet ferrite materials, which realize unidirectional transmission and reverse isolation of radio frequency signals under the drive of external magnetic steel. It is particularly pointed out that the presence of external magnetic steel will inevitably increase the height of the entire system, which is contrary to the development of micro-integration of the entire system. Hexagonal spin ferrite materials have both high remanence ratio Mr / M s and the anisotropy field H a , a large "internal field" can be generated inside the ferrite, causing the magnetic moment to precess under the action of the microwave field without an external magnetic steel. This characteristic of hexagonal ferrite materials can be used to provide a self-bias field for the operation of microwave devices, completely get rid of the constraints of external magnetic steel, and achieve micro-integration. Therefore, the development of C-band self-biased hexagonal ferrite materials is of great significance.

[0003] For self-biased hexagonal spin ferrite materials, Oakland University (J.Appl.Phys., 2009, 105, 023908) used floating zone melting to prepare BaAl x Fe 12-x O 19 Hexagonal ferrite material; performance indicators are: anisotropy field H a Adjustable between 17 and 34 kOe, ferromagnetic resonance line width ΔH ≤ 150 Oe, remanence ratio M not reported r / M s , coercive force H c and dielectric loss tanδ ε The University of Electronic Science and Technology of China and Northeastern University (Materials, 2022, 15, 8792) used the traditional solid phase sintering method to prepare Ba 0.8 La 0.2 Fe 11.8 Cu 0.2 O 19 Hexagonal ferrite material; performance indicators are: remanence ratio M r / M s =0.89, coercive force H c =2813Oe, anisotropy field H a =14.6kOe, ferromagnetic resonance linewidth ΔH = 379Oe, dielectric loss tanδ not reported ε Patent CN202310320907.5 discloses a self-biased hexagonal ferrite gyromagnetic material and its preparation method, using La-Co-Zn to replace BaFe 12 O 19 Hexagonal ferrite material; performance indicators are: remanence ratio M r / M s =0.91, coercive force H c =2909Oe, anisotropy field H a =13.0kOe, ferromagnetic resonance linewidth ΔH = 461Oe, dielectric loss tanδ not reported ε The anisotropy field H of the above materials a ≥9kOe, which is not suitable for C-band micro-integrated device design. a ≤9kOe), Northeastern University (J.Am.Ceram.Soc., 2008, 91, 2952) used traditional solid phase sintering method to prepare BaFe 11.1 Sc 0.9 O 19 Hexagonal ferrite material, its performance indicators are: remanence ratio M r / M s =0.92, coercive force H c =1430Oe, anisotropy field H a =8kOe, ferromagnetic resonance linewidth ΔH = 530Oe, dielectric loss tanδ not reported ε Jawaharlal Nehru University in India (J.Alloys.Compd., 2018, 736, 266-275) used the sol-gel method to prepare BaM / YIG composite gyromagnetic ferrite materials. The study showed that as the YIG content increased, the anisotropic field H a Gradually decreases, the ferromagnetic resonance line width ΔH decreases from 2000Oe to 385Oe, but the coercive force H c <600Oe, dielectric loss tanδ not reported ε The coercivity H of the above materials is c ≤2.5kOe, it is impossible to ensure that the magnetic moment is arranged along the c-axis under external perturbations; and the ferromagnetic resonance linewidth ΔH ≥300Oe, the insertion loss of the designed micro-integrated device is bound to be large. Summary of the invention

[0004] The purpose of the present invention is to solve the problem that the C-band ultra-low loss self-biased hexagonal spin ferrite material involved in the current technology is difficult to meet the engineering requirements of low loss and wide bandwidth of C-band micro-integrated devices, and to propose a C-band ultra-low loss self-biased hexagonal spin ferrite material and a preparation method thereof. The material has both high and adjustable anisotropy field H a , high coercivity H c and remanence ratio M r / M s , ultra-low ferromagnetic resonance linewidth △H and dielectric loss tanδ ε The characteristics of this device can fundamentally solve the engineering needs of the above-mentioned C-band micro-integrated devices.

[0005] The core idea of ​​the present invention is to grow a high M nanostructured ferrite on the surface of low-loss BiCaZrVIn-YIG gyromagnetic ferrite particles. r / M s and H c The characteristic LaScBiCu-BaM hexagonal ferrite material. In the BiCaZrVIn-YIG ferrite formula system, a proper amount of Fe-deficient formula and the introduction of high-valent Zr 4+ and V 5+ Can reduce electrons in Fe 2+ ~Fe 3+ Migration between the two electrodes reduces the dielectric loss tanδ ε ;Bi 3+ The outer 6p electrons have strong spin-orbit coupling and covalent bond formation capabilities, which improve the dielectric constant of YIG spin ferrite materials and match the dielectric constant of BaM hexagonal spin ferrite materials; low melting point Bi 3+ and V 5+ It can reduce the sintering temperature of YIG ferrite materials and achieve densification sintering; 3+ It is beneficial to reduce the anisotropy of YIG gyromagnetic ferrite materials, thereby reducing the ferromagnetic resonance line width ΔH. In the LaScBiCu-BaM gyromagnetic ferrite formula system, Sc 3+ Mainly occupying the 2b crystal position, significantly reducing the anisotropy of BaM gyromagnetic ferrite materials; La 3+ Cu in equilibrium system 2+ valence state; combined with low melting point Bi 3+ and Cu 3+ , high melting point La 3+ and Sc 3+The competition mechanism enables the preparation of uniform and dense ferrite microcrystals. In addition, based on the diffusion mechanism, LaScBiCu-BaM hexagonal ferrite forms a concentration gradient near the grain boundary of BiCaZrVIn-YIG ferrite. During the remagnetization process, the highly anisotropic LaScBiCu-BaM hexagonal ferrite can hinder the formation and expansion of the remagnetization core of BiZrVIn-YIG ferrite, significantly improving the coercivity H. c In terms of additive system, the introduction of La 2 O 3 、SiO 2 and SrTiO 3 Nano ceramic powder and other dopants, among which La 2 O 3 On the one hand, it can repair the lattice defects of LaScBiCu-BaM hexagonal ferrite, and on the other hand, it can regulate the SrTiO 3 The order of nano-ceramic powder forms an ultra-high resistance state, which is enriched around the ferrite grains and significantly reduces the dielectric loss tanδ ε ;SiO 2 It can narrow the particle size distribution, improve the orientation degree and remanence ratio M r / M s That is, the highly anisotropic hexagonal ferrite "locks" the magnetic moment of the surrounding YIG ferrite to increase the coercive force H. c and remanence ratio M r / M s ; Through the YIG ferrite and BaM hexagonal ferrite dual-phase composite and In 3+ Sc 3+ Plasmon substitution significantly reduces the anisotropy field H a ; Low melting point and high melting point ions are introduced through the main formula, SiO 2 Additives refine grains, La 2 O 3 Additives repair lattice defects, regulate grain boundary characteristics, and reduce the ferromagnetic resonance line width ΔH; high-valent ions and Fe deficiency are introduced through the main formula to inhibit Fe 2+ Generate, La 2 O 3 Modified SrTiO 3 Nano-ceramic powder is concentrated near the ferrite grains to form a high resistance state, reducing the dielectric loss tanδ ε .

[0006] The key technical problem solved by the present invention is that it is difficult for the C-band ultra-low loss self-biased hexagonal spin ferrite material to have both high and adjustable anisotropy field H a , high coercivity H c and remanence ratio M r / M s, ultra-low ferromagnetic resonance linewidth △H and dielectric loss tanδ ε The developed material has both high and adjustable anisotropy field H a , high coercivity H c and remanence ratio M r / M s , ultra-low ferromagnetic resonance linewidth △H and dielectric loss tanδ ε Characteristics. The technical solution adopted by the present invention is as follows:

[0007] A C-band ultra-low loss self-biased hexagonal spin ferrite material, including BiCaZrVIn-YIG spin ferrite material and LaScBiCu-BaM hexagonal spin ferrite material;

[0008] The BiCaZrVIn-YIG gyromagnetic ferrite material composition includes 10.5-13.5 mol% Bi 2 O 3 , 7.5~14.5mol%CaCO 3 10.5~15.5mol%ZrO 2 , 0.5~5.5mol%V 2 O 5 、0.5~4.5mol%In 2 O 3 、12.5~18.5mol%Y 2 O 3 and 40.5~48.5mol%Fe 2 O 3 ; LaScBiCu-BaM hexagonal ferrite material composition includes 0.5-3.5mol% La 2 O 3 、3.5~10.5mol%Sc 2 O 3 、1.5~7.5mol%Bi 2 O 3 , 2.5~9.5mol% CuO, 8.5~15.5mol% BaCO 3 and 63.5~75.5mol%Fe 2 O 3 ; The weight ratio of BiCaZrVIn-YIG hexagonal ferrite material to LaScBiCu-BaM hexagonal ferrite material is 0.1 to 10;

[0009] The weight percentage of dopant in C-band ultra-low loss self-biased hexagonal ferrite material, calculated as oxide: 0.3-0.7wt.% La 2 O3 、0.4~0.8wt.%SiO 2 and 0.5~0.9wt.%SrTiO 3 .

[0010] A method for preparing a C-band ultra-low loss self-biased hexagonal spin-magnetic ferrite material comprises the following steps:

[0011] Step 1: Ingredients

[0012] Bi 2 O 3 、CaCO 3 、ZrO 2 、V 2 O 5 、In 2 O 3 , Y 2 O 3 and Fe 2 O 3 As raw materials, according to "10.5-13.5 mol% Bi 2 O 3 , 7.5~14.5mol%CaCO 3 10.5~15.5mol%ZrO 2 , 0.5~5.5mol%V 2 O 5 、0.5~4.5mol%In 2 O 3 、12.5~18.5mol%Y 2 O 3 and 40.5~48.5mol%Fe 2 O 3 " Weigh the raw materials in a ratio of 1:1 and mix them to obtain BiCaZrVIn-YIG gyromagnetic ferrite raw materials;

[0013] Step 2: First ball milling

[0014] The BiCaZrVIn-YIG ferrite raw materials obtained in step 1 are ball-milled and mixed uniformly by a planetary ball mill, and the ball-milling time is 2 to 6 hours;

[0015] Step 3: Primary sintering

[0016] The ball mill obtained in step 2 is dried and sieved, and sintered at 1000-1200° C., with a heating rate of 1.5-3.5° C. / min and a holding time of 3-6 h;

[0017] Step 4: Secondary ball milling

[0018] Take La 2 O3 Sc 2 O 3 、Bi 2 O 3 , CuO, BaCO 3 and Fe 2 O 3 As raw materials, according to "0.5~3.5mol%La 2 O 3 、3.5~10.5mol%Sc 2 O 3 、1.5~7.5mol%Bi 2 O 3 , 2.5~9.5mol% CuO, 8.5~15.5mol% BaCO 3 and 63.5~75.5mol%Fe 2 O 3 " Weigh each raw material in a ratio of 0.1 to 10, and mix them to obtain a LaScBiCu-BaM hexagonal ferrite raw material; add the LaScBiCu-BaM hexagonal ferrite raw material to the primary sintered material obtained in step 3, and mix them evenly in a planetary ball mill for 18 to 30 hours;

[0019] Step 5: Secondary sintering

[0020] The secondary ball mill obtained in step 4 is dried and sintered at 1200-1300° C. for 3-6 hours;

[0021] Step 6: Doping

[0022] In the secondary sintered material obtained in step 5, add the dopant according to the mass percentage of the secondary sintered material: 0.3-0.7wt.% La 2 O 3 、0.4~0.8wt.%SiO 2 and 0.5~0.9wt.%SrTiO 3 ;

[0023] Step 7: Three-time ball milling

[0024] The mixture obtained in step 6 is ball-milled in a planetary ball mill for 18 to 30 hours, and the particle size of the powder is controlled between 0.6 and 0.9 μm;

[0025] Step 8: Magnetic field forming

[0026] The tertiary ball milled material obtained in step 7 is pressed and molded in a magnetic field molding machine, the molding magnetic field is 0.7-1.2T, and the molding pressure is 90-150MPa;

[0027] Step 9: Three-time sintering

[0028] The green body obtained in step 8 is sintered three times, the sintering temperature is 1200-1300° C., and the holding time is 8-16 hours; after the sintering is completed, it is naturally cooled to room temperature and taken out to obtain the C-band ultra-low loss self-biased hexagonal spin magnet ferrite material.

[0029] Furthermore, in step 5, the temperature is increased to 1200-1300° C. at a heating rate of 5-20° C. / min and kept at this temperature for 3-6 hours.

[0030] Furthermore, in step 9, the temperature is raised to 1200-1300° C. at a heating rate of 5-20° C. / min and kept at this temperature for 8-16 hours.

[0031] The performance test of the C-band ultra-low loss self-biased hexagonal spin ferrite material obtained in step 9 is as follows: saturation magnetization intensity 4πM s , residual magnetization 4πM r , coercive force H c Measured using the American LakeShore 8604 vibrating sample magnetometer; ferromagnetic resonance line width ΔH and dielectric loss tanδ ε The anisotropic field H is measured using the CK-XW-100 high-frequency integrated measurement system. a The final technical indicators of the C-band ultra-low loss self-biased hexagonal spin-magnetic ferrite material prepared by the present invention are as follows:

[0032] Saturation magnetization 4πM s ≥3150Gs;

[0033] Remanence ratio M r / M s ≥0.90;

[0034] Coercivity H c ≥2.5kOe;

[0035] Anisotropy field H a ≤8.5kOe;

[0036] Ferromagnetic resonance line width ΔH≤280Oe;

[0037] Dielectric loss tanδ ε ≤3×10 -3 .

[0038] The C-band ultra-low loss self-biased hexagonal spin ferrite material provided by the present invention can solve the following key technical problems in the fields of microwave device design: (1) high saturation magnetization intensity (4πM s ≥3150Gs) can meet the engineering requirements of microwave device bandwidth expansion; (2) high remanence ratio (M r / M s ≥0.90) and coercivity (H c ≥2.5kOe) can make the magnetic moment tend to precess in the direction of strong anisotropy, forming a built-in field, completely freeing itself from the constraints of external magnetic steel and achieving micro-integration; (3) high and adjustable anisotropy field (H a ≤8.5kOe) can meet the design requirements of micro-integrated devices in the C-band range; (4) ultra-low ferromagnetic resonance linewidth (ΔH≤280Oe) and dielectric loss (tanδ ε ≤3×10 -3 ) can meet the engineering requirements of low insertion loss of micro-integrated devices.

[0039] Compared with the prior art, the present invention has the following beneficial effects:

[0040] In a C-band ultra-low loss self-biased hexagonal gyromagnetic ferrite material provided by the present invention, BiCaZrVIn-YIG gyromagnetic ferrite is a cubic crystal system, has multiple easy magnetization axes, and has a small particle gap; LaScBiCu-BaM hexagonal gyromagnetic ferrite is a hexagonal crystal system, has a single easy magnetization axis, and has a large particle gap; LaScBiCu-BaM hexagonal gyromagnetic ferrite is grown on the surface of BiCaZrVIn-YIG gyromagnetic ferrite particles, and since the distance between the two phase particles is small and the exchange coupling effect is strong, the composite material has both high M r / M s and H c At the same time, LaScBiCu-BaM hexagonal ferrite is interspersed between BiCaZrVIn-YIG ferrite grains with smaller gaps, so the density of the composite material is larger and ΔH is smaller; in addition, BiCaZrVIn-YIG ferrite has multiple easy magnetization axes, and the growth of LaScBiCu-BaM hexagonal ferrite is inevitably affected by it, the induced anisotropy is weakened, and it has a smaller H a In addition, the high-resistance SrTiO 3 Concentrated around ferrite grains, significantly reducing dielectric loss tanδ ε .

[0041] Based on the above, the present invention proposes a C-band ultra-low loss self-biased hexagonal spin ferrite material and a preparation method thereof, which grows a high M on the surface of low-loss BiCaZrVIn-YIG spin ferrite particles. r / M s and Hc The LaScBiCu-BaM hexagonal ferrite with high and adjustable anisotropy field H a , high coercivity H c and remanence ratio M r / M s , ultra-low ferromagnetic resonance linewidth △H and dielectric loss tanδ ε The characteristic hexagonal spin magnetic ferrite material meets the engineering requirements of low loss and wide bandwidth for C-band micro-integrated devices. BRIEF DESCRIPTION OF THE DRAWINGS

[0042] Figure 1 This is a scanning electron microscope photograph of the C-band ultra-low loss self-biased hexagonal spin-magnetic ferrite material in Example 1;

[0043] Figure 2 This is a scanning electron microscope photograph of the C-band ultra-low loss self-biased hexagonal spin-magnetic ferrite material in Example 4;

[0044] Figure 3 This is a ferromagnetic resonance line width fitting diagram of the C-band ultra-low loss self-biased hexagonal spin ferrite material in Example 1;

[0045] Figure 4 This is a ferromagnetic resonance linewidth fitting diagram of the C-band ultra-low loss self-biased hexagonal spin ferrite material in Example 4. DETAILED DESCRIPTION

[0046] Aiming at the engineering demand problem of low-loss and wide bandwidth expansion of C-band micro-integrated devices, the present invention provides a C-band ultra-low-loss self-biased hexagonal spin-magnetic ferrite material and a preparation method thereof, which overcomes the problem that the existing C-band ultra-low-loss self-biased hexagonal spin-magnetic ferrite material is difficult to have both high and adjustable anisotropic field H a , high coercivity H c and remanence ratio M r / M s , ultra-low ferromagnetic resonance linewidth △H and dielectric loss tanδ ε The technical difficulties of growing high M on the surface of low-loss BiCaZrVIn-YIG gyromagnetic ferrite particles r / M s and H c The LaScBiCu-BaM hexagonal spin ferrite material with unique characteristics is developed. The correlation mechanism of key parameters of C-band ultra-low loss self-biased hexagonal spin ferrite material is deeply analyzed by using ion occupancy regulation mechanism, anisotropy compensation mechanism, magnetization resistance mechanism, ion diffusion mechanism, etc. The formation mechanism of ferrite grain interaction coupling is clarified by combining grain growth dynamics and phase boundary characteristics; the best main formula and additive formula are formulated, and the key preparation technology is optimized and regulated, and finally a material with high and adjustable anisotropy field H is prepared. a, high coercivity H c and remanence ratio M r / M s , ultra-low ferromagnetic resonance linewidth △H and dielectric loss tanδ ε Characteristic C-band ultra-low loss self-biased hexagonal spin-magnetic ferrite material.

[0047] The technical solution of the present invention is described in detail below in conjunction with the accompanying drawings and embodiments.

[0048] Example

[0049] A method for preparing a C-band ultra-low loss self-biased hexagonal spin-magnetic ferrite material specifically comprises the following steps:

[0050] Step 1: Ingredients

[0051] Bi 2 O 3 、CaCO 3 、ZrO 2 、V 2 O 5 、In 2 O 3 , Y 2 O 3 and Fe 2 O 3 As raw materials, various raw materials are weighed and mixed according to the proportions shown in the following table to obtain BiCaZrVIn-YIG gyromagnetic ferrite raw materials; the main formula of BiCaZrVIn-YIG gyromagnetic ferrite materials in Examples 1 to 4 is shown in the following table:

[0052]

[0053] Step 2: First ball milling

[0054] The BiCaZrVIn-YIG ferrite raw materials obtained in step 1 were ball-milled and mixed uniformly using a planetary ball mill for 4.5 h.

[0055] Step 3: Primary sintering

[0056] The ball mill obtained in step 2 was dried and sieved, and sintered at 1060°C, with a heating rate of 2.5°C / min and a holding time of 3.5h;

[0057] Step 4: Secondary ball milling

[0058] Take La 2 O 3 Sc 2 O 3 、Bi 2 O 3 , CuO, BaCO3 and Fe 2 O 3 As raw materials, each raw material is weighed according to the proportion shown in the following table, and mixed to obtain LaScBiCu-BaM hexagonal ferrite raw material; according to the weight ratio of BiCaZrVIn-YIG ferrite raw material to LaScBiCu-BaM hexagonal ferrite raw material of 3.6:6.4, LaScBiCu-BaM hexagonal ferrite raw material is added to the primary sintered material obtained in step 3, and the mixture is evenly milled in a planetary ball mill for 21 hours; the main formula of LaScBiCu-BaM hexagonal ferrite raw material in Examples 1 to 4 is shown in the following table:

[0059]

[0060] Step 5: Secondary sintering

[0061] The secondary ball mill obtained in step 4 is dried and sintered at 1200-1300° C. for 4.5 h;

[0062] Step 6: Doping

[0063] In the secondary sintered material obtained in step 5, add the dopant according to the mass percentage of the secondary sintered material: 0.55wt.%La 2 O 3 、0.45wt.%SiO 2 and 0.75wt.% SrTiO 3 ;

[0064] Step 7: Three-time ball milling

[0065] The mixture obtained in step 6 was ball-milled in a planetary ball mill for 24 hours, and the particle size of the powder was controlled between 0.7 and 0.8 μm;

[0066] Step 8: Magnetic field forming

[0067] The tertiary ball milled material obtained in step 7 is pressed and molded in a magnetic field molding machine, the molding magnetic field is 0.9T, and the molding pressure is 120MPa;

[0068] Step 9: Three-time sintering

[0069] The green body obtained in step 8 is sintered three times, the sintering temperature is 1260° C., and the holding time is 12 hours; after the sintering is completed, it is naturally cooled to room temperature and taken out to obtain the C-band ultra-low loss self-biased hexagonal spin-magnetic ferrite material.

[0070] The performance test of the C-band ultra-low loss self-biased hexagonal spin ferrite material obtained in step 9 is as follows: saturation magnetization intensity 4πM s, residual magnetization 4πM r , coercive force H c Measured using the American LakeShore 8604 vibrating sample magnetometer; ferromagnetic resonance line width ΔH and dielectric loss tanδ ε The anisotropic field H is measured using the CK-XW-100 high-frequency integrated measurement system. a It is derived from Kittel's formula.

[0071] The C-band ultra-low loss self-biased hexagonal spin-magnetic ferrite material prepared based on the above process, the performance parameters of Examples 1 to 4 are as follows:

[0072]

Claims

1. A C-band ultra-low loss self-biased hexagonal spin-magnetic ferrite material, characterized in that: Including BiCaZrVIn-YIG gyromagnetic ferrite materials and LaScBiCu-BaM hexagonal gyromagnetic ferrite materials; The BiCaZrVIn-YIG gyromagnetic ferrite material components include 10.5-13.5mol% Bi2O3, 7.5-14.5mol% CaCO3, 10.5-15.5mol% ZrO2, 0.5-5.5mol% V2O5, 0.5-4.5mol% In2O3, 12.5-18.5mol% Y2O3 and 40.5-48.5mol% Fe2O3; LaScBiCu-BaM hexagonal gyromagnetic The ferrite material components include 0.5-3.5 mol% La2O3, 3.5-10.5 mol% Sc2O3, 1.5-7.5 mol% Bi2O3, 2.5-9.5 mol% CuO, 8.5-15.5 mol% BaCO3 and 63.5-75.5 mol% Fe2O3; the weight ratio of BiCaZrVIn-YIG gyromagnetic ferrite material and LaScBiCu-BaM hexagonal gyromagnetic ferrite material is 0.1-10; The weight percentage of the dopant in the C-band ultra-low loss self-biased hexagonal spin ferrite material is calculated as oxides: 0.3-0.7wt.% La2O3, 0.4-0.8wt.% SiO2 and 0.5-0.9wt.% SrTiO3.

2. A method for preparing a C-band ultra-low loss self-biased hexagonal spin-magnetic ferrite material, characterized in that: The following steps are involved: Step 1: Ingredients Bi2O3, CaCO3, ZrO2, V2O5, In2O3, Y2O3 and Fe2O3 are used as raw materials, and the raw materials are weighed and mixed according to the ratio of "10.5-13.5mol% Bi2O3, 7.5-14.5mol% CaCO3, 10.5-15.5mol% ZrO2, 0.5-5.5mol% V2O5, 0.5-4.5mol% In2O3, 12.5-18.5mol% Y2O3 and 40.5-48.5mol% Fe2O3" to obtain BiCaZrVIn-YIG gyromagnetic ferrite raw materials; Step 2: First ball milling The BiCaZrVIn-YIG gyromagnetic ferrite raw material obtained in step 1 is ball-milled for 2 to 6 hours; Step 3: Primary sintering The ball mill obtained in step 2 is dried and sieved, and sintered at 1000-1200° C. for 3-6 hours; Step 4: Secondary ball milling Using La2O3, Sc2O3, Bi2O3, CuO, BaCO3 and Fe2O3 as raw materials, weigh the raw materials according to the ratio of "0.5-3.5mol% La2O3, 3.5-10.5mol% Sc2O3, 1.5-7.5mol% Bi2O3, 2.5-9.5mol% CuO, 8.5-15.5mol% BaCO3 and 63.5-75.5mol% Fe2O3", and mix the raw materials to obtain LaScBiCu-BaM hexagonal ferrite raw materials; according to the weight ratio of BiCaZrVIn-YIG ferrite material to LaScBiCu-BaM hexagonal ferrite material being 0.1-10, add the LaScBiCu-BaM hexagonal ferrite raw materials to the primary sintered material obtained in step 3, and mix them evenly by ball milling, and the ball milling time is 18-30h; Step 5: Secondary sintering The secondary ball mill obtained in step 4 is dried and sintered at 1200-1300° C. for 3-6 hours; Step 6: Doping In the secondary sintered material obtained in step 5, dopants are added according to the mass percentage of the secondary sintered material: 0.3-0.7wt.% La2O3, 0.4-0.8wt.% SiO2 and 0.5-0.9wt.% SrTiO3; Step 7: Three-time ball milling The mixture obtained in step 6 is ball-milled for 18 to 30 hours, and the particle size of the powder is controlled between 0.6 and 0.9 μm; Step 8: Magnetic field forming The tertiary ball milled material obtained in step 7 is pressed into a mold, the molding magnetic field is 0.7-1.2T, and the molding pressure is 90-150MPa; Step 9: Three-time sintering The green body obtained in step 8 is sintered three times, the sintering temperature is 1200-1300° C., and the holding time is 8-16 hours; after the sintering is completed, it is naturally cooled to room temperature and taken out to obtain the C-band ultra-low loss self-biased hexagonal spin magnet ferrite material.

3. The method for preparing the C-band ultra-low loss self-biased hexagonal spin-magnetic ferrite material according to claim 2, characterized in that: In step 3, the temperature is raised to 1000-1200° C. at a heating rate of 1.5-3.5° C. / min and kept at this temperature for 3-6 hours.

4. The method for preparing the C-band ultra-low loss self-biased hexagonal spin-magnetic ferrite material according to claim 2, characterized in that: In step 5, the temperature is raised to 1200-1300° C. at a heating rate of 5-20° C. / min and kept at this temperature for 3-6 hours.

5. The method for preparing the C-band ultra-low loss self-biased hexagonal spin-magnetic ferrite material according to claim 2, characterized in that: In step 9, the temperature is raised to 1200-1300° C. at a heating rate of 5-20° C. / min and kept at this temperature for 8-16 hours.

Citation Information

Patent Citations

  • Self-biased hexagonal ferrite gyromagnetic material and preparation method thereof

    CN116217217A

  • Two-phase composite ferrite material for X-band self-biased device and preparation method of two-phase composite ferrite material

    CN115579203A

  • Magnetic body for high frequency

    JP2001052913A